Not Out of the Woods: Preserving the Human in Environmental Architecture. (1st February 2005) - Light, Andrew; Wallace, Aurora
Abstract : The North American environmental movement has historically sought to redress the depletion and degradation of natural resources that has been the legacy of the industrial revolution. Predominant in this approach has been the preservation of wilderness, conservation of species biodiversity and the restoration of natural ecosystems. While the results of such activity have often been commendable, several scholars have pointed out that the environmental movement has inherited an unfortunate bias against urban environments, and consequently, a blind spot to ways in which densely populated built spaces can serve to enhance rather than degrade efforts to achieve sustainability. After exploring this concern we argue that environmental architecture can serve as a counter-balance to this bias, focused, as it is, on the ways in which the construction and organisation of built spaces for humans can help or hinder the pursuit of environmental priorities. But if environmental architecture is to take this role then it must be understood in a broader context, one which does not exclude other moral, political and aesthetic values in the production of human environments. We will highlight several examples of how environmental architecture has combined success and failure at taking a broader view of environmental questions, with a specific focus on one green skyscraper that may be good for the natural environment but not necessarily for the human environment of the city.